Uwagi o rzeźbie greckiej i nowych kierunkach jej badań - Bugaj, Ewa (Folia Praehistorica Posnaniensia, 2016)
In the paper concerning the new approaches in the study of Greek sculptural production at first the author considers the problem of putting the ancient artefacts with the modern works of art on the same level and the need for the new conceptualisation of them. In the next step she outlines historiography of the Greek sculpture with the particular reference to the study on its stylistic development. Further on the author presents selected, new approaches in the study on Greek sculpture, the ones which are breaking the long tradition of research on them, rooted in the Enlightenment and Hegelian thought and historicism. She focusses on the results of these research which shift the interpretative emphasis from the relation between the image/sculpture and its model to that of the image and its viewer.